2016
DOI: 10.1016/j.celrep.2016.08.029
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis of the InR/PI3K/Akt Network Identifies the Dynamic Response to Insulin Signaling

Abstract: Summary Insulin regulates an essential conserved signaling pathway affecting growth, proliferation and metabolism. To expand our understanding of the insulin pathway, we combine biochemical, genetic and computational approaches to build a comprehensive Drosophila InR/PI3K/Akt network. First, we map the dynamic protein-protein interaction network surrounding the insulin core pathway using bait-prey interactions connecting 566 proteins. Combining RNA interference screening and phospho-specific antibodies, we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 32 publications
3
78
0
Order By: Relevance
“…) and the gene Psa , known to interact with the major IIS/TOR core component Akt1 (Vinayagam et al. ). Similarly, among the loci that differentiate the LE populations from the other EE populations we identified Tomosyn , a regulator of insulin secretion with a confirmed role in aging in C. elegans (Ch'ng et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and the gene Psa , known to interact with the major IIS/TOR core component Akt1 (Vinayagam et al. ). Similarly, among the loci that differentiate the LE populations from the other EE populations we identified Tomosyn , a regulator of insulin secretion with a confirmed role in aging in C. elegans (Ch'ng et al.…”
Section: Resultsmentioning
confidence: 99%
“…discussion in Remolina et al 2012;Fabian et al 2018;Flatt and Partridge 2018), we only found a few loci in this signaling network among our candidates. For instance, among the loci significantly differentiated between the E and P populations, we identified the TOR signaling gene happyhour (Bryk et al 2010;Khan et al 2012) and the gene Psa, known to interact with the major IIS/TOR core component Akt1 (Vinayagam et al 2016). Similarly, among the loci that differentiate the LE populations from the other EE populations we identified Tomosyn, a regulator of insulin secretion with a confirmed role in aging in C. elegans (Ch'ng et al 2008), as well as Pi3K21B and PKCδ, which both play a role in signal transduction from the insulin receptor (Braiman et al 2001;Teleman 2010).…”
Section: Different From 'Canonical' Longevity Genesmentioning
confidence: 99%
“…Interestingly, this gene set was not enriched in MCF10A cells that had lost PTEN [77]. A study mapping the dynamic protein-protein interaction network within the core insulin signalling pathway in Drosophila also found significant enrichment for proteins involved in 'centrosome duplication' following 10 and 30 minutes of insulin stimulation [78].…”
Section: Pik3ca/aktmentioning
confidence: 97%
“…Several other studies support a reciprocal relationship between the PI3K pathway and centrosomal regulation. An RNAi screen in Drosophila thus identified proteins involved in the centrosome cycle as regulators of acute insulin-dependent AKT activation [78]. Microtubule acetylation has also recently been linked to sequestration and inhibition of AKT [127].…”
Section: Impact Of Pi3k On Centrosomes (And Vice Versa)mentioning
confidence: 99%
“…However, the global regulatory network of insulin action via protein phosphorylation has not thus far been elucidated (Buescher et al, ; Chiappino‐Pepe, Pandey, Ataman, & Hatzimanikatis, ; Hatzimanikatis & Saez‐Rodriguez, ; Hyduke, Lewis, & Palsson, ; Joyce & Palsson, ; Palsson & Zengler, ). Phosphoproteomic studies of insulin signaling have been performed with Drosophila cells (Friedman et al, ; Vinayagam et al, ), 3T3‐L1 mouse adipocytes (Humphrey et al, ), mouse hepatoma cells (Monetti, Nagaraj, Sharma, & Mann, ), mouse brown preadipocytes (Krüger et al, ), rat primary hepatocytes (Zhang, Zhang, & Yu, ), rat Fao hepatoma cells (Yugi et al, ) and mouse hepatoma (Humphrey, Azimifar, & Mann, ). Among these phosphoproteomic studies, the cellular functions of insulin‐dependent protein phosphorylation have been estimated using databases of prior knowledge such as GO (Friedman et al, ; Humphrey, Azimifar, et al, ; Vinayagam et al, ; Zhang et al, ), whereas insulin‐dependent regulatory networks of protein phosphorylation by kinases have been estimated using KSR inference (Humphrey et al, ; Miller et al, ).…”
Section: Introductionmentioning
confidence: 99%